Early Development and Putative Primordial Germ Cells Characterization in Dogs - Martins, D. S.; Ambrosio, C. E.; Saraiva, N. Z. [UNESP]; Wenceslau, C. V.; Morini, A. C.; Kerkis, I.; Garcia, J. M. [UNESP]; Miglino, M. A. (Wiley-Blackwell Publishing, Inc, 2011)
ContentsPreviously, three distinct populations of putative primordial germ cells (PGCs), namely gonocytes, intermediate cells and pre-spermatogonia, have been described in the human foetal testis. According to our knowledge, these PGCs have not been studied in any other species. The aim of our study was to identify similar PGC populations in canine embryos. First, we develop a protocol for canine embryo isolation. Following our protocol, 15 canine embryos at 21-25 days of pregnancy were isolated by ovaryhysterectomy surgery. Our data indicate that dramatic changes occur in canine embryo development and PGCs specification between 21 to 25 days of gestation. At that moment, only two PGC populations with distinct morphology can be identified by histological analyses. Cell population 1 presented round nuclei with prominent nucleolus and a high nuclear to cytoplasm ratio, showing gonocyte morphology. Cell population 2 was often localized at the periphery of the testicular cords and presented typical features of PGC. Both germ cell populations were positively immunostained with anti-human OCT-4 antibody. However, at day 25, all cells of population 1 reacted positively with OCT-4, whereas in population 2, fewer cells were positive for this marker. These two PGCs populations present morphological features similar to gonocytes and intermediate cells from human foetal testis. It is expected that a population of pre-spermatogonia would be observed at later stages of canine foetus development. We also showed that anti-human OCT-4 antibody can be useful to identify canine PGC in vivo.